Implementation of Work-Life Balance to Enhance Employee Productivity - Rostini Rostini; Asmar Asmar; A Fadel Muhammad (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Work-life balance has become an important issue in the modern workplace, especially with the increasing adoption of hybrid and remote work systems. This study aims to explore employees' experiences in managing the balance between work and personal life demands and its impact on productivity. Using a qualitative approach, in-depth interviews were conducted with 12 participants with diverse backgrounds and work arrangements. The results showed that work time flexibility, organizational support, and ability in workload management were the main factors influencing work-life balance. Employees who have work flexibility generally show higher levels of job satisfaction and productivity than those who experience imbalance. However, challenges such as excessive workload and unrealistic company expectations remain significant barriers to achieving this balance. This study highlights the importance of companies' role in formulating policies that not only support work-life balance administratively, but also build a work culture that cares about mental health, well-being, and the sustainability of employee productivity in the long term.